Fast multiple-symbol detection for free-space optical communications - Riediger, Michael L. B.; Schober, Robert; Lampe, Lutz (IEEE Transactions on Communications, 2009)
In this paper, we investigate noncoherent detection, i.e. detection assuming the absence of channel state information at the receiver, of on-ff keying in an intensity modulation and direct detection (IM/DD) free-space optical (FSO) system. To partially recover the performance loss associated with symbol- by-symbol noncoherent detection, we consider the application of multiple-symbol detection (MSD), in which block-wise decisions are made using an observation window of several bit intervals. Specifically, we develop a fast search algorithm for optimal MSD and propose a reduced-complexity decision metric suitable for suboptimal MSD; performance results confirm that the optimal and suboptimal metrics perform comparably well. Significantly, the complexity of our receiver, on a per bit-decision basis, is only logarithmically dependent on the observation window size. We also present the framework for a decision-feedback receiver and obtain performance expressions for the ideal case of error-free feedback; these expressions serve as an upper bound to the performance of MSD. Analytical and simulation results indicate that as the observation window size increases, the performance of the MSD receiver approaches that of detection with channel state information. The conclusion is reached that the proposed implementation provides an attractive low-complexity mechanism for performing noncoherent MSD in FSO systems. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Atmospheric turbulence; Decision-feedback; Free-space optical communication; Multiple-symbol detection; Noncoherent detection